find the value of the polynomial p(x) =x^3 -6x^2+9x+7 at X+1​

Question

find the value of the polynomial p(x) =x^3 -6x^2+9x+7 at X+1​

in progress 0
Katherine 2 weeks 2021-11-25T04:51:47+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-11-25T04:53:25+00:00

    Answer:

    Step-by-step explanation:

    ANSWER:-

    Given:-

    • We need to find the value of polynomial
    • We will place the value of x simply and solve the equation.

    \sf{x^3-6x^2+9x+7}

    \sf{x+1=0}\\\sf{x= -1}

    So, placing the Equations further:-

    \sf{(-1)^3-6(-1)^2+9(-1)+7}

    \sf{-1-6-9+7}\\\sf{-16+7}\\\sf{=-9}

    So, -9 is the answer.

    Things to Note:-

    • Always when attempting these questions, equate the value of x to zero
    • Here, I took the x+1 equal to zero to find the value of x
    • Always use BODMAS technique to simplify
    • Brackets of Division, Multiplication, Addition and Subtraction is the full form
    • It states that Division is the first step to be carried out
    • Followed by Multiplication, Addition and at last subtraction
    • If any step is not followed answer may/might be wrong.
    • Odd powers:-
    • Positive remains the same and Negative also remains the same
    • Even powers:-
    • Positive remain the same
    • But negative changes to positive.
    0
    2021-11-25T04:53:26+00:00

    Given :

    p(x) =  {x}^{3}  - 6 {x}^{2}  + 9x + 7

    Solution :

    x + 1 \:  \:  \:  \:  \:  \:  \:  \:  \:  \: \: (given)

    Let x + 1 = 0

    x = -1

    p(x) =  {x}^{3}  - 6 {x}^{2}  + 9x + 7

    p( - 1) =  {( - 1)}^{3}  - 6 \times  {( - 1)}^{2}  + 9 \times ( - 1) + 7

    p( - 1) =  - 1 - 6 \times 1 - 9 + 7

    p( - 1) =  - 1 - 6 - 2

    p( - 1) =  - 9

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )